1998
DOI: 10.1159/000055454
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Lead, Cadmium and Calcium in Cataractous Lenses

Abstract: Lenticular copper, lead, cadmium and calcium levels were measured using atomic absorption spectrophotometry in 9 normal and 37 cataractous human lenses. The nuclear parts of the lenses were used for the study in both groups. The lenticular deposition of these four elements in cataract was statistically significant. In the cataractous group, males had higher levels of cadmium compared to females. No lead was detected in normal lenses. The calcium content was significantly higher in cortical cataract whereas the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
3
19
0
3
Order By: Relevance
“…Our data concerning the apparently higher levels of both Fe and Cu in cataractous vs healthy ' control ' lenses are in general agreement with earlier studies (Cekic, 1998 ;Cekic et al, 1999 ;Cook and McGahan, 1986 ;Lakomaa and Eklund, 1978 ;Nath et al, 1969). However, while the storage and processing of these control lenses was conducted in the same manner as the cataractous lenses (see ' materials and methods ') we cannot draw firm conclusions regarding the levels of these metals in healthy vs cataractous lenses, as the sample sources and histories are dissimilar.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data concerning the apparently higher levels of both Fe and Cu in cataractous vs healthy ' control ' lenses are in general agreement with earlier studies (Cekic, 1998 ;Cekic et al, 1999 ;Cook and McGahan, 1986 ;Lakomaa and Eklund, 1978 ;Nath et al, 1969). However, while the storage and processing of these control lenses was conducted in the same manner as the cataractous lenses (see ' materials and methods ') we cannot draw firm conclusions regarding the levels of these metals in healthy vs cataractous lenses, as the sample sources and histories are dissimilar.…”
Section: Discussionsupporting
confidence: 93%
“…The total amounts of Fe and Cu detected in these non-cataractous lenses were lower than in both types of cataractous lens (Fig. 4), consistent with previous observations (Cekic, 1998 ;Cekic et al, 1999 ;Cook and McGahan, 1986 ;Lakomaa and Eklund, 1978 ;Nath et al, 1969).…”
Section: Comparison Of Type II and Type Iv Lensessupporting
confidence: 91%
“…Cekic correlated cigarette smoking and cadmium accumulation in the lens and concluded that nicotine and additional fillers from cigarettes might have additional heavy metals ions, and smoking might be cataractogenic [38]. The deposition of various ions in the lenticule might be different in both genders, or might result in cataract morbidity [39]. Again, for further understanding ionic impact on organisms and the environment, many studies need yet be performed.…”
Section: Metals and Sight Organmentioning
confidence: 99%
“…Although this technique does not discriminate between different heavy metals, since Fe and Cu are the most abundant redox-active intralenticular metal ions (Cekic, 1998;Cekic et al, 1999), it can be used to estimate both redox availability and localization of these metals at the cellular level. Formalin-®xed lenses were sectioned and incubated at 228C in 2 % (w/v) glutaraldehyde in 0 .…”
Section: Demonstration Of Lenticular Redox-active Heavy Metals By Autmentioning
confidence: 99%
“…In general, there appear to be higher levels of Fe and Cu present in human cataractous lenses compared to healthy controls (Lakomaa and Eklund, 1978;Eckhert, 1983;Cook and McGahan, 1986;Garland, 1990;Cekic, 1998;Cekic et al, 1999;Garner et al, 2000). However, it is not certain where these metals are located within the lens nor to what degree they are available for participation in redox reactions that could generate free radicals; HO Á in particular (Garner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%